The determinant factors of Indonesian competitiveness of cocoa exports to Germany - Tyas Titi Hapsari; Aisyah Fitri Yuniasih (Department of Development Economics, Universitas Sriwijaya, 2020)
Cocoa is one of the leading commodities from the plantation sub-sector in Indonesia. At the world level, Indonesia is the third-largest producer of cocoa beans after Côte d’Ivoire and Ghana (FAO, 2017). However, Indonesia still exports cocoa in the form of (raw) beans which results in the loss of added value and not developing the domestic cocoa industry. For this reason, the government issued No. 67/PMK.011/ 2010 concerning the imposition of Export Levy and Export Levy Tariffs to suppress the export of cocoa beans and then increase the competitiveness of processed cocoa exports. The purpose of this study was to determine the competitiveness performance of Indonesian processed cocoa to Germany and what factors influenced the export competitiveness in 1992-2017. This study uses secondary data from various sources that were analyzed using Revealed Comparative Advantage (RCA) and Error Correction Mechanism (ECM). The analysis shows that in the long run the variable exchange rate, world cocoa prices, and dummy export duty significantly affect competitiveness while in the short term, population variables and world cocoa prices significantly influence competitiveness.